Carbamylated albumin is one of the target antigens of anti-carbamylated protein antibodies. (7th April 2017) - Nakabo, Shuichiro; Hashimoto, Motomu; Ito, Shinji; Furu, Moritoshi; Ito, Hiromu; Fujii, Takao; Yoshifuji, Hajime; Imura, Yoshitaka; Nakashima, Ran; Murakami, Kosaku; Kuramoto, Nobuo; Tanaka, Masao; et al.
Abstract: Objectives. Anti-carbamylated protein (anti-CarP) antibodies are detected in RA patients. Fetal calf serum is used as an antigen source in anti-CarP ELISA, and the precise target antigens have not been found. We aimed to identify the target antigens of anti-CarP antibodies. Methods. Western blotting of anti-CarP antibodies was conducted. Anti-carbamylated human albumin (CarALB) antibody was detected by in-house ELISA for 493 RA patients and 144 healthy controls (HCs). An inhibition ELISA of anti-CarP antibodies by CarALB and citrullinated albumin (citALB) was performed using eight RA patients' sera. Serum CarALB was detected by liquid chromatography–tandem mass spectroscopy (LC/MS/MS), and the serum MPO concentration was measured by ELISA. Results. We focused on carbamylated albumin because it corresponded to the size of the thickest band detected by western blotting of anti-CarP antibodies. Anti-CarALB antibody was detected in 31.4% of RA patients, and the correlation of the titres between anti-CarALB and anti-CarP was much closer than that between anti-citALB and anti-CCP antibodies (ρ = 0.59 and ρ = 0.16, respectively). The inhibition ELISA showed that anti-CarP antibodies were inhibited by CarALB, but not by citALB. CarALB was detected in sera from RA patients by LC/MS/MS. The serum MPO concentration was correlated with disease activity and was higher in RA patients with anti-CarALB antibody than in those without. Conclusion. We found that carbamylated albumin is a novel target antigen of anti-CarP antibodies, and it is the first reported target antigen that has not been reported as the target of ACPA.